HEALTH LAW IMPLEMENTATION REALIZES GENDER EQUALITY AND WOMEN'S EMPOWERMENT - Siregar, Rospita; Hendri Jayadi (Sociae Polites, 2023)
The millennium development program (MDGs) in quality health services, including women's reproductive health, is not evenly distributed, due to poor infrastructure and the unequal quality of health services between provinces. It is hoped that Indonesian Health has succeeded in achieving most of Indonesia's MDGs targets, namely 49 of the 67 MDGs indicators can be improved. In normative juridical research, law is conceptualized as norms or rules that apply in society. Using a statutory approach and a conceptual approach in health law. There is a guarantee of a sense of security in accordance with Article 28G Paragraph (1) of the 1945 Constitution, thereby providing women's rights in accordance with the mandate given by the state and guaranteeing rights without discrimination and gender differences. There is the Convention on the Elimination of All Forms of Discrimination against Women, which emphasizes that women's human rights are respected, then women's reproductive health rights have also been formulated by the International Planned Parenthood Federation (IPPF) since 1996, namely the right to equality and freedom from all forms of discrimination. In the end, support for women's empowerment must involve many parties from politics, PUG institutions, Human Resources, Budget, Gender Analysis Tools, and Community Participation. Keywords: gender equality, health law, reproductive health rights